The Connection between the Distance of the Suppliers and the Keeping of the Safety Stock - Gábor Farkas (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
The objective of this research is revealing the connection between the distance of the suppliers and the keeping of the safety stock respectively the provision of the safety times when establishing the logistics strategy of the companies. In this article it will be analyzed when it is worth inserting safety time and when it is justified to holding safety stock so that the base materials, auxiliary materials and parts required for the production can be provided continuously according to the requirements. It will be assumed, that the increase of the distance does not always mean the increase of the transportation time as far as the directions are concerned. In this article, factors that play – besides the distance - a role in the variation of the transportation time are presented. In this research the proportion with which the size of the safety stock and the safety time required for the production when the distance is increasing are defined. Regarding the analyses products with various values, dimensions and needs of utilization are compared. In the final section is determined when it is worth choosing a supplier within a shorter geographic distance and in case of which products it is worth opting for the product that is offered at a lower price but being at a bigger distance.
Keywords: R4; 330; transportation; supplier selection; decision support systems; stock piling